Euro 5 경유 대형트럭의 유해대기오염물질 배출특성 - 홍희경; Heekyoung Hong; 문선희; Sunhee Mun; 서석준; Seokjun Seo; 김정화; Jounghwa Kim; 정성운; Sungwoon Jung; 정택호; Taekho Chung; et al. (한국분무공학회지, 2018)
Emission characteristics of regulated pollutants (CO, NOx, HC and PM) and hazardous air pollutants (HAPs) from diesel heavy duty trucks equipped with EGR+pDPF and SCR for Euro 5 emission standards were investigated using a chassis dynamometer. In the case of regulated pollutants, diesel heavy duty trucks with EGR+pDPF emitted 79% less CO than those with SCR. Also, those with the SCR emitted 36% less NOx than those with the EGR+pDPF. The results of VOCs have show that alkanes emissions for heavy duty trucks with the EGR+pDPF and the SCR have been higher than alkenes, cycloalkanes and aromatics. In the case of individual VOCs, the highest of propene emissions for 11.3~16.1% occupied. For aromatics group, benzene emissions are the highest percentage for 4.4~15.5%. In the future, the results of present study will provide basic data to set up HAPs emissions inventory for mobile source.